Nastajanje prve glasbene šole v Slovenski Istri - Gombač, Marija (Annales. Series historia et sociologia, 1998)
After the Second World War, the general economic restoration was immediately followed by a rapid development of the educational system, culture and art in Slovene Istra as well, although the period of an all-round development began only after the signing of the London Memorandum in October 1954. In spite of the fact that only a few concerts were held there it can be said that the social activities in villages and towns were quickly resumed. Various choirs, folklore and recitation groups were formed. The history of the Koper School ofMusic, the first school of this kind on Slovene Istra, dates back to 1948 when founded, in Portorož, by the pedagogue, conductor and pianist Srečko Kumar (1888-1954) ...
Keywords: glasba; glasbene šole; Koper; music; Slovenian Istria; Slovenska Istra